1977
DOI: 10.1007/bf01940933
|View full text |Cite
|
Sign up to set email alerts
|

Na and Cl transport across the isolated turtle colon: Parallel pathways for transmural ion movement

Abstract: Summary. Transmural fluxes of 3H-mannitol and 22Na or a6CI were measured simultaneously in portions of isolated turtle colon stripped of serosal musculature. The relationships between mannitol flux and the flux of Na or C1 are characteristic of simple diffusion and suggest that transmural mannitol flow is largely confined to a paracellular pathway where Na, C1 and mannitol move much as in free solution. The contribution of"edge damage" to the transmural mannitol flow appears to be minimal. Mucosal hyperosmolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 33 publications
10
62
0
Order By: Relevance
“…This concept has been supported experimentally in growtharrested cells which show no decrease in TER as monolayers age despite the properties of the TJs being similar to those in dividing cell monolayers [27]. Consistent with the development of effective occluding junctions, monolayers of 16HBE14o-or Calu-3 cells were found to develop a low permeability to the cell impermeant sugar, mannitol [28].…”
Section: Discussionmentioning
confidence: 71%
“…This concept has been supported experimentally in growtharrested cells which show no decrease in TER as monolayers age despite the properties of the TJs being similar to those in dividing cell monolayers [27]. Consistent with the development of effective occluding junctions, monolayers of 16HBE14o-or Calu-3 cells were found to develop a low permeability to the cell impermeant sugar, mannitol [28].…”
Section: Discussionmentioning
confidence: 71%
“…The partial ionic conductances for Na' and C1-(JQs', J's) accounted for -70% of G. We do not know whether the greater disparity between the sum of the partial ionic conductances for Na' and Ct-and G in CF tissues reflects the contribution ofan active component to G, e.g., associated with the greater Na+ transport rate, or an unmeasured ion. Mannitol permeability coefficients, a marker of paracellular permeability (19,20), were not different for any of the three groups.…”
Section: Resultsmentioning
confidence: 82%
“…(Frizzell et al 1976) and in isolated toad colon (Dawson, 1977) have also indicated that Na and Cl movements from blood to lumen are consistent with diffusion through a nondiscriminating barrier. In our experiments, the entire flux of these ions into the lumen appeared due to simple diffusion as in the dialysis membrane model and no appearances in the impulse response functions suggested that any other process was involved.…”
Section: Discussionmentioning
confidence: 92%
“…The observed unidirectional fluxes across the epithelium result from the total movement through both routes and various methods have been used in vitro in an attempt to dissect the total flux into its components. Electrical effects, the changes in ionic movements occurring with applied currents and the use of labelled molecules, such as urea or mannitol, as markers for the paracellular pathway, have all been explored (Mandel & Curran, 1972;Frizzell, Koch & Schultz, 1976;Dawson, 1977). The method described in the present paper was devised to enable studies of the transport pathways to be made in vivo and in such a way that would allow future investigations of the effects of various modifying factors such as drugs,…”
Section: Introductionmentioning
confidence: 99%